Unusual oral findings of the toxic epidermal necrolysis in an HIV-infected patient: a case report - Vieira,Vinicius da Costa (2019)
ABSTRACT Erythema multiforme (EM), Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis (TEN) have been reported as possible adverse effects of some classes of first-line antiretroviral drugs (ART) for HIV treatment. Herein we report an unusual presentation of TEN lesions associated with ART in an HIV-infected patient. The patient presented disseminated cutaneous eruption and oral lesions from the lips to the oropharynx region, causing odynophagia and dysphagia. In the tongue, circular, atypical erythematous lesions appeared, increasing in diameter over seven days and coalescing since then to complete remission. TEN treatment included efavirenz interruption, use of methylprednisolone, prophylactic antibiotic, and daily laser therapy with low-intensity red light. The circular oral lesions have not been described yet. Reporting our findings and clinical management may help diagnosing other similar cases and guide the clinical conduct. Analgesia and acceleration of oral ulcer repair with red laser therapy are recommended.